Nursing Care For Schizophrenia Patients With Mindfullness Therapy Intervention In The Mentari Room Muhammadiyah Lamongan Hospital - Nisa, Fitrotin; Sholikah, Siti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Schizophrenia is a type of mental disorder that is often found. Schizophrenia is a disease that affects the brain and causes strange and disturbed thoughts, perceptions, emotions, movements, behavior. The prevalence of schizophrenia is estimated at around 1% of the world's population. 5 clients with a medical diagnosis of schizophrenia with nursing problems of sensory perception disorders in the Mentari ward of Muhammadiyah Lamongan Hospital. The research design uses descriptive in the form of a case review. The approach used is nursing care which includes assessment, nursing diagnosis, planning, implementation and evaluation. The results of the implementation of nursing care for 5 patients obtained the same nursing diagnosis, namely sensory perception disorders. The problem of sensory perception disorders in 5 patients was partially resolved within 2-3 implementations. The healing process differs for each patient, due to the history of illnesses that aggravate the patient's condition, such as hypertension, age, nutrition, and psychological control which are different for each patient. From the results of this study it can be concluded that mindfulness therapy techniques can be implemented in patients diagnosed with schizophrenia. because it can increase the control of hallucinations in clients. Keywords: Nursing Care, Schizophrenia, Mindfulness Therap